The Effect Of Capital Structure, Profitability, And Liquidity On Company Value In Coal Subsector Mining Companies Listed On The Indonesia Stock Exchange 2019-2023 Period - Irwan, Valenius; Diana Riyana Harjayanti (Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of capital structure, profitability, and liquidity on firm value. The object of this research is coal sub-sector mining companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research uses a quantitative approach with a descriptive-associative method. The sampling technique applied is purposive sampling, resulting in seven selected companies as the research sample. The secondary data collected were analyzed using panel data regression with the assistance of EViews 13 software. The results show that, partially, capital structure as measured by Debt to Equity Ratio (DER) and profitability as measured by Return on Assets (ROA) have a positive and significant effect on firm value. Conversely, liquidity as measured by CR does not have a significant effect on firm value (PBV). Simultaneously, the three independent variables have a significant effect on firm value as measured by PBV. The adjusted R-squared value of 0.3940 indicates that 39.40% of the variation in firm value can be explained by capital structure, profitability, and liquidity, while the remaining 60.60% is explained by other factors outside the model. These findings indicate that capital structure and profitability play an important role in explaining changes in firm value in the coal sub-sector examined in this study.